2013
DOI: 10.1007/s00586-013-2695-7
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative pelvic axial rotation: a possible predictor for postoperative coronal decompensation in thoracolumbar/lumbar adolescent idiopathic scoliosis

Abstract: Background The pelvis as the biomechanical foundation of spine, plays an important role in the balance of the stance and gait through the multi-link spinal-pelvic system. If the pelvic axial rotation (PAR) exists in adolescent idiopathic scoliosis (AIS) patients, it should theoretically have some effects on the body balance. Purpose To explore the probable effects of preoperative PAR on the spinal balance in coronal plane in AIS patients with main thoracolumbar/lumbar (TL/L) curve after posterior spinal instru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The pelvic axial rotation has been investigated by many authors. 6,7,[11][12][13] Gum et al concluded that the PR in the transverse plane was in the same direction of the apical thoracic vertebral rotation in major thoracic curves (Lenke 1, 2, and 3 curve types) and that Lenke 1 and 2 curve types without a compensatory thoracolumbar or lumbar curve did not have the predicted rotation. 6 Zhao et al 7 defined physiological PR as left/right ratio within the range of 1 + 0.1, whereas Lucas et al 12 defined the normal range of convex/concave ratio as from 0.95 to 1.05.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pelvic axial rotation has been investigated by many authors. 6,7,[11][12][13] Gum et al concluded that the PR in the transverse plane was in the same direction of the apical thoracic vertebral rotation in major thoracic curves (Lenke 1, 2, and 3 curve types) and that Lenke 1 and 2 curve types without a compensatory thoracolumbar or lumbar curve did not have the predicted rotation. 6 Zhao et al 7 defined physiological PR as left/right ratio within the range of 1 + 0.1, whereas Lucas et al 12 defined the normal range of convex/concave ratio as from 0.95 to 1.05.…”
Section: Discussionmentioning
confidence: 99%
“…Qiu et al performed a retrospective study in 38 AIS patients with thoracolumbar/lumbar curve and found that in patients with pelvic axial rotation, there was a higher incidence of coronal decompensation. 13…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure a proper orthogonal view, all radiographs were assessed on both views for adequacy. Orthogonal accuracy has previously been expressed as a comparative distance of ASIS to SI distance on either side [33]; however, this was not available for all patients. Instead, the distance from the S1 spinous process was measured to the most lateral aspect of the sciatic notch (S1–SN) as seen in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…It was found in another study [15] that preoperative PR might be related to postoperative loss of balance in the coronal plane. All these conclusions seem to suggest that axial balance may affect coronal balance, though more research is needed to elucidate the intrinsic association between them.…”
Section: Discussionmentioning
confidence: 99%